Vernacular architecture and traditional urbanism in the World Heritage Cultural Landscape Property of Pico, in Azores (Portugal) - Florentino, Rui (2022)
The World Heritage Committee lists every year, several cultural sites as World Heritage properties. Some of these properties balance the notion of a landscape that bears combined works between nature and men, on which vernacular architecture is part of a local tradition of interaction with nature. The 3dPast research project is a European project, coordinated by Escola Superior Gallaecia and co-funded by the European Union, under the Creative Europe programme. The project studies and values vernacular knowledge of these unique places. In Portugal, the Pico landscape was listed as a World Heritage property due to the 500 years of history of local inhabitants adapting farming practices to produce wine, in a challenge environment and in a remote place in the middle of the Atlantic. This article aims to study, the history and the development of the island's architecture and urbanism, based on an ancestral way of life that is still alive nowadays. The scarcity of natural resources and the difficulties to travel between villages and islands emphasised the effects of insularity. However, the continuity of local culture, passed down through generations, created a strong identity, which is source of pride. The cultural landscape classified area includes about 987 hectares, from the parish of Criação Velha, on the south coast, to Santa Luzia, on the north side, covering part of two municipalities of Pico. The article first presents a brief historical background of the island. Following, it focuses on the evolution of human occupation, through the reading of population indicators and traditional architecture and urbanism, recognizing the unique cultural and landscape values within the property. Finally, it discusses the current regulatory framework on territorial planning, and the architectural and urban regulations in planning framework, with particular emphasis on processes and practices at different scales.